Efeito do pré-aquecimento e da pós-polimerização nas propriedades mecânicas e grau de conversão de um compósito experimental reforçado com fibra de vidro - Almeida, Letícia Nunes de (2016)
The pre-heating and post-curing can improve the mechanical properties of composites, even though there be no studies of fiber reinforced composites. The aim of this study was to evaluate the effect of pre-heating and post-curing autoclave and microwave in flexural strength (FS), diametral tensile strength (DTS), knoop microhardness (KHN) and degree of conversion (DC) of a experimental fiber- reinfoced composite. The experimental material was prepared with 30% glass fibers (3 mm), 22.5% of the resin matrix (40/60 Bis-GMA / TEGDMA) and 47.5% barium silicate particles. Six experimental groups were created by the interaction between the factors under study: heating, on two levels (without heating and heating at 60°C) and post-curing in 3 levels (conventional curing without post-curing, autoclave (120°C for 15 minutes) and microwaves (540 W for 5 minutes) The groups were: F - curing at 1500 mW/cm2 for 40 seconds; F + M - curing and post- polymerization in microwave; F + A - curing and post-curing in an autoclave , AQ + F - the composite heating prior to curing, AQ + F + M - heating prior to curing and post-curing in microwave;. AQ + F + A - heating prior to curing and post-curing and autoclave heating was conducted digital oven for 5 minutes at 60°C. Ten samples of the RF dimensions 25 x 2 x 2 mm and DTS in dimensions of 3 x 6 mm were tested in a universal testing machine Instron 5965, 0.5 mm/min. the KHN test was performed on samples of 3 x 6 mm with a load of 50 g for 30 sec, totaling 50 indentations per group. GC was obtained by Spectroscopy Fourier Transform Infrared (FTIR) on 5 samples. Data were analyzed by a factorial 2x3 and general linear model ANOVA and Tukey tests (α = 0.05). Factor analysis showed significant interaction between the factors just for RTD (p = 0.0001); preheating was significant factor for RF (p = 0.0001), RTD (p = 0.020) and KHN (p = 0.0001); post-curing factor for KHN was significant (p = 0.0001). ANOVA and Tukey tests showed statistically significant differences between groups for DTS (p = 0.001: AQ + F ≥ AQ + F + M = F + A = AQ + F + A = F + M ≥ F), FS (p = 0.016: AQ + F + M ≥ AQ + F + A + F = AQ = AQ + A + M ≥ F ≥ F) and KHN (p = 0.0001: AQ + F + M ≥ AQ + A + F = F = F + A + M ≥ F ≥ M + AQ). GC results showed no statistically significant difference. Through the Pearson correlation coefficient was observed significant positive correlation between the GC and RTD (r = 0.473, p = 0.008) and between DTS and FS (r = 0.263, p = 0.042). The pre-heating and post- polymerization were shown to be favorable to promote better mechanical properties of fiber reinforced composite by studied, specific for each property being analyzed.